(3QSGdI GdQTO hGdgOGjIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3fU GdeLJHi CNfhN GdChGf hEOQjS GdReGf gQeS GdgQGeSI GdfaS GdcdjI s
(3BNQgG (B:s
(3aGSeYhG eYGTQ GdChdjGA fU gPG GdQSGdI GdJi hVYJgG hSeJjgG GdQTO hGdgOGjI jSJQTO HgG GdWGdHhf hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B40s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds